ANALISIS YURIDIS TERHADAP PERTIMBANGAN HAKIM DALAM PUTUSAN PERKARA TINDAK PIDANA TERORISME BERDASARKAN UNDANG-UNDANG NO. 5 TAHUN 2018 TENTANG PEMBERANTASAN TINDAK PIDANA TERORISME - Adzi Rizki; Daniel Hendrawan (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN RAHMAT HUSADA, 2025)
All studies discuss the crime of terrorism, particularly in the context of judges' decisions and use court decisions as the main object, namely the decision of the district court in East Jakarta. The problems in this study are 1) The legal regulatory mechanism in examining and deciding cases of terrorism crimes? and 2) How is the law enforcement against terrorism cases in Indonesia? This research method uses normative legal research with secondary data. The approaches used are the statutory approach, conceptual and case approach. The analysis used is qualitative. The results of this study indicate that the legal regulatory mechanism in examining and deciding cases of terrorism crimes has carried out legal considerations by paying attention to the juridical, factual, and philosophical aspects in cases of terrorism crimes. The judge carefully examined the criminal elements in the indictment, particularly regarding the defendant's involvement in a banned organization and participation in semi-military military training that leads to terror goals. The application of the principle of legal certainty in Decision Number 812/Pid.Sus/2021/PN Jkt.Tim has been applied by the panel of judges by explicitly referring to the relevant statutory provisions, namely Law Number 5 of 2018 concerning the Eradication of Criminal Acts of Terrorism.